Cohabitation of independent sets and dominating sets in trees - Löwenstein, Christian,; Rautenbach, Dieter, (Utilitas Mathematica, 2011)
We give a constructive characterization of trees that have a maximum independent set and a minimum dominating set which are disjoint and show that the corresponding decision problem is NP-hard for general graphs.